URGENSI ALTRUISME DAN HARDINESS PADA RELAWAN PENANGGULANGAN BENCANA ALAM: SEBUAH STUDI KEPUSTAKAAN [THE URGENCY OF ALTRUISM AND RESILIENCE IN NATURAL DISASTER MANAGEMENT VOLUNTEERS: A LITERATURE STUDY] - Rahmat, Hayatul Khairul; Pernanda, Syahti; Casmini, C; Budiarto, Arief; Pratiwi, Suandara; Anwar, Moh Khoerul (Perkumpulan Ahli Bimbingan Konseling Islam Indonesia, 2021)
Indonesia is a country prone to natural disasters. Dealing with the negative impacts caused by natural disasters is not an easy matter but requires various parties who collaborate to handle them, such as volunteers. The author aims to examine the urgency of altruism and hardiness in natural disaster relief volunteers. The findings of this study are volunteers, namely people who voluntarily give their time, energy, and money to help other people affected by natural disasters. Seeing the sad reality, namely natural disasters that cause many casualties. it is very important for a disaster management volunteer to have altruism and hardiness because with these two attitudes a disaster management volunteer is able to be useful to the people around him.